Institutional Framework and Regulatory Challenges in the Development of the Sharia Financial Sector in Indonesia: A Political Economy Perspective - Soumena, Fadly Yashari; Anwar, Anas Iswanto; Arsyad, Rahmat; Laming, Ripa Fajarina; Bahasoan, Awal Nopriyanto (Universitas Muhammadiyah Makassar, 2023)
This study aims to examine the institutional framework and regulatory challenges in the development of the Sharia financial sector in Indonesia.The main objectives of this research are to analyze the role of government institutions and regulatory bodies, as well as to identify regulatory barriers, in order to strengthen the institutional framework and support the growth of the Sharia financial sector in Indonesia.This study utilizes qualitative research to analyze the institutional framework and regulatory challenges in Indonesia's Sharia financial sector from a political economy perspective. Data will be gathered from policy documents, legal regulations, government reports, academic publications, case studies, and expert interviews. The analysis will involve content analysis for policy documents and regulations, interview analysis, and descriptive analysis of statistical data on the sector's growth.Overall, the results of the analysis show that through this active participation, the Indonesian government hopes to strengthen Indonesia's image as the global financial center of Shariah and the country's economic position at the international level. Thus, the role of the Indonesian government in the Sharia financial sector is expected to continue to grow, provide greater benefits to Indonesians, and strengthen Indonesia's position at the international level. Increased intensive collaboration between governments, practitioners, and colleges in the form of development programs to produce competent human resources (HRM) finance. Providing stronger policy incentives and support The government needs to provide stronger incentives and policy support to develop Sharia finance in Indonesia. Encourage the development of innovative Sharia financial products.